Nature, nurture and egalitarian policy: what can we learn from molecular genetics? - Petter Lundborg; Anders Stenberg (Institute for the Study of Labor (IZA), 2009)
This brief paper draws attention to molecular genetic research which may provide a new dimension to our understanding of how socioeconomic outcomes are generated. In particular, we provide an overview of the recently emerging evidence of gene-environment interaction effects. This literature points out specific policy areas which may compensate individuals carrying genetic risks, without resorting to gene mapping of the population. Such policies would also increase intergenerational mobility if genetic and/or environmental risk factors are more common in socially disadvantaged groups.
Keywords: J62; H50; 330; Gene; environment; interaction; molecular genetics; inequality; Gentechnik; Natur; Soziale Ungleichheit; Sozialpolitik; Generationenbeziehungen; Soziale Mobilität